Pengaruh self concept terhadap kemampuan berpikir tingkat tinggi mata pelajaran matematika siswa kelas VIII F SMPN 1 Mataram - Sri Radiatun Wahida; Baidowi Baidowi; Ulfa Lu'luilmaknun; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2021)
This study aims to describe and determine the effect of self-concept on higher-order thinking skills of class VIII SMPN 1 Mataram in the academic year 2020/2021. This type of research is included in ex post facto research, with a sample of 32 students of class VIII F SMPN 1 Mataram in the 2020/2021 academic year. Students fill out and complete self-concept questionnaires and test questions for higher order thinking skills. The results showed that (1) Self-concept owned by 3.13% students was categorized as very good, 21.87% students were in good category, 62.5% students were in quite good category, and 12.5% ​​students were in low category. Meanwhile, for higher order thinking skills, there are 3.13% of students in very good category, 21.87% of students in good category, 62.5% of students in good enough category, 9.37% of students in poor category and 3, 13% of students in the very poor category. (2) There is an effect of self concept on higher order thinking ability with regression equation Y = 1.283 + 0.787X.